Sumber daya kesehatan dan unmet need: analisis tingkat provinsi - Lilik Ariyanti; Djaswadi Dasuki; Siswanto Agus Wilopo (Berita Kedokteran Masyarakat (BKM), 2017)
Availability of health resources and unmet needs: a provincial level analysisPurposeThis study aimed to analyze the association between the availability of health and percentage of unmet needs in every province in Indonesia.MethodsThis study used secondary data of the Indonesian demographic and health survey 2012, health facilities research report 2011, Board of Population and Family Planning contraceptive services report 2012 and reports from Indonesian Central Bureau of Statistics 2012. The sample was all provinces in Indonesia. Linear regression tests were used to examine the correlation between the availability of health resources and unmet needs.ResultsStatistically, there was no association between the ratio of health resources by 10,000 population with unmet needs for family planning. But, there was an association between the ratio of health resources based on the area with unmet needs for family planning. The higher ratio of health resources by 1000 km2, the lower unmet need percentage for family planning.ConclusionsAvailability (quantity and distribution) of health resources based on the area plays an important role in family planning programs especially unmet needs for family planning. Planning of health resources provision should not be only based on the ratio by 10,000 population, but also consider the area of services.